Measures of opportunity and the calculation of the arson rate: The connection between operationalization and association - Pettiway, Leon E. (Journal of quantitative criminology, 1985)
The crime of arson is complicated in part because of the motives associated with the offense and the vast assortment of combustible objects or targets deliberately burned in urban areas. This research attempts to conceptualize the crime in light of criminal law and demonstrates that arson occupies a rather unique position. Although classified as a property crime, the legislative intent appears to focus on the protection of human life. Moreover, legislative developments have brought us to the point where burning almost any property is designated arson. There is a growing concern over the incidence of arson, but there has been little discussion of how to calculate the arson rate when the targets of opportunity are not known. The exploratory research presented here addresses the structure of arson rates by using an assortment of indirect and direct measures of opportunity as denominators in the calculation of the arson rate. Factor analysis reduces a 27×27 correlation matrix to six significant factors and demonstrates that some measures share the same underlying rate structure. By using a factorbase scale (dependent variable) for each factor and a set of independent variables, regression analysis reveals that there are differences in the direction of association, the degree of association, and the types of independent variables that associate with different measures of the arson rate.